MinPlotX: A powerful tool for formula recalculation, visualization, and comparison of large mineral compositional datasets - Walters Jesse B.; Gies Nils B. (Mineralogia)
MinPlotX is an open-source software for mineral formula recalculation and compositional plotting providing an easy-to-use stand-alone graphical user interface (GUI) as well as an advanced programming interface (API). The aim of MinPlotX is to provide publication-ready tables of mineral formulae and plots of mineral composition. The new GUI-based approach allows for a wider variety of calculation and plotting options, including both commonly used pre-defined mineral specific diagrams and a large variety of multi-dimensional diagrams that can be created quickly and easily by the user. The most powerful feature is the addition of nearly any kind of numerical or categorized metadata, such as sample name, analysis location, trace element concentration, age, and others, that can be used to subdivide or contour data. The modular nature of the program makes it possible to add new mineral formula recalculation and plotting routines, as well as other data science tools, without changing the overall structure of the program. Therefore, MinPlotX provides advanced users the means to add new routines and interact with the program through the API, while simultaneously providing a simple and effective platform for users who have no programming experience or do not have access to MATLAB®.